Minimising Coerciveness in Coercion: A Case Study of Social Work Powers under the Victorian Mental Health Act. Issue 4 (2nd October 2017) - Maylea, Chris
ABSTRACT: The balance between care and control in mental health social work is one of constant tension. In the State of Victoria, Australia, the Mental Health Act 2014 gives coercive powers to social workers employed by public mental health services. These include the power to decide if a person needs to be assessed by a psychiatrist, to "take" a person using bodily restraint, to enter premises, and to search and seize a person's belongings. This paper applies a doctrinal analysis to examine the law, then argues that the use of these powers by social workers, where safe, may be less restrictive than when they are used by police or paramedics. The exercise of these powers may be less traumatic and stigmatising to the people who are subject to them, and social workers may be both legally and ethically obligated to use coercion when appropriate. IMPLICATIONS More social work literature on the coercive powers under mental health legislation is needed as well as more guidance on using these powers for social workers in practice. In some circumstances, these coercive powers may be better exercised by social workers than by other professionals. Social workers should carefully consider their legal and ethical obligations to use these powers in some circumstances.